1992
DOI: 10.1152/jappl.1992.73.4.1232
|View full text |Cite
|
Sign up to set email alerts
|

Hypohydration affects forearm vascular conductance independent of heart rate during exercise

Abstract: Elevated body core temperature stimulates cutaneous vasodilation, which can be modified by nonthermal factors. To test whether hypohydration affects forearm vascular conductance discretely from relative alterations in heart rate (HR), eight trained cyclists exercised progressively for 20 min each at 60, 120, and 180 W [approximately 22, 37, and 55% of maximal cycling O2 consumption (VO2peak), respectively] in a warm humid environment (dry bulb temperature 30 degrees C; wet bulb temperature 24 degrees C). Esoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Although it has been suggested that fluid ingestion during exercise can prevent the adverse effects of dehydration on endurance performance (39,44), there are no adequately controlled studies which have directly addressed this hypothesis. Furthermore, most such studies have been performed at low (<50% ofTO2max; 11, 12,23,36,41) or moderately low (<60% VO2max) exercise intensities (3,7,42) over prolonged periods leading to large fluid losses. Conclusions from these studies may not apply to more intense (>70% VO2max), prolonged (>90 mm) exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been suggested that fluid ingestion during exercise can prevent the adverse effects of dehydration on endurance performance (39,44), there are no adequately controlled studies which have directly addressed this hypothesis. Furthermore, most such studies have been performed at low (<50% ofTO2max; 11, 12,23,36,41) or moderately low (<60% VO2max) exercise intensities (3,7,42) over prolonged periods leading to large fluid losses. Conclusions from these studies may not apply to more intense (>70% VO2max), prolonged (>90 mm) exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Other work has reported moderate hypohydration (4 % body mass loss) to blunt mean BP responses during exercise with an ambient temperature of 40 °C, but not in ambient temperatures between 10 and 30 °C in young male adults (Kenefick, Sollanek, Charkoudian, & Sawka, 2014). Another study in young male adults reported similar BP responses during cycling exercise in mild heat (30 °C) following 24‐hr fluid restriction (Tankersley, Zappe, Meister, & Kenney, 1985). A more recent study in young male adults reported lower absolute mean BP during exercise following mild and moderate hypohydration (2 and 3.5 % body mass loss, respectively), but this study elicited hypohydration via exercise in the heat (37 °C) (Pearson et al., 2013).…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies demonstrate sweat rate varies widely depending on exercise intensity, environment and clothing worn (Tankersley et al. ; Gill et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the environment and work rate may not have produced enough stress on the CV system to significantly alter SBF or sweat response. Previous studies demonstrate sweat rate varies widely depending on exercise intensity, environment and clothing worn (Tankersley et al 1992;Gill et al 2000). In addition, the participants' baseline fitness level may have impacted their sweat rate.…”
Section: Pre-interventionmentioning
confidence: 99%